A Critical Pathway for Mass Casualty Incident Preparedness. Issue 4 (July 2021) - Moran, Mary E.; Blecker, Nathan; Gothard, M. David; George, Richard L.
Abstract : Background: Rates of mass casualty incidents (MCIs) have been on the rise in the United States, highlighting the need for health care systems to have an emergency response plan. Trauma centers are fundamental during MCIs and serve a crucial leadership role in preparedness for them. Objective: The purpose of this study was to describe the design and implementation of simulated MCI drills at an American College of Surgeons verified Level I trauma center in the Midwest. Methods: A quasi-experimental time-series design was utilized to determine MCI simulation effects on staff performance using an emergency department checklist to measure emergency department throughput time. A multidisciplinary MCI design team developed a checklist for the emergency department, which identified tasks required to complete it. The 16-item checklist, Critical Pathway Management methodology, was used to identify the critical pathway for patient throughput during a surge. Two in situ MCI simulation drills were conducted in the emergency department (October and December 2019), and Critical Pathway Management identified the primary patient throughput rate limiters as notification and inpatient nursing staff presentation. Results: Emergency department throughput decreased from a mean of 15 to 11 min (reduction of 26.7%) between the two time periods after focusing on rate-limiting tasks. Conclusion: This quality improvement project demonstrated that the use of institution-specific checklists and Critical Pathway Management to identify critical pathways and potential rate limiters led to patient throughput improvements.